Usage and Acceptability of Electronic Human Resource Management (e-HRM) in Pakistani Organizations - Ayesha Zareef; Adnan Jamil; Shazia Hassan (UW Journal of Management Sciences, 2022)
Introduction: Today is the era of development in information technology. From the past IT has increased benefits as well as opportunities for both individuals and organizations. The demand for E-HRM adoption and its implementation is increasing with every passing day. This paper aims to facilitate organizations to recognize and know the importance of adoption and implementation of electronic human resource management in Pakistan, to point out and recognize the factors affecting individuals to use E-HRM, and to contribute to the literature on E-HRM. Methodology: Relationship between Perceived performance expectancy, Perceived effort expectancy, Social influence, Facilitation condition, Intentions to adopt and Actual use is explained using UTAUT model. Questionnaire was distributed among 149 professionals working in different organizations in Rawalpindi and Islamabad. Before hypothesis testing several tests have been conducted such as descriptive analysis, correlation, and reliability test. Furthermore, SPSS has been used for hypothesis testing. Findings: The findings of this research study has underlined important aspects which are affecting the adoption, implementation and actual use of technology in organizations working in Pakistan, it has given empirical evidence for the applicability of UTAUT to the adoption of technology (Rozee.pk) through survey of 149 Rozee.pk users. From the results it is observed that both effort and performance expectancy notably affect intention towards using Rozee.pk towards the actual use of technology.